The Role of the Triple Helix Model in Promoting the Circular Economy: Government-Led Integration Strategies and Practical Application - Maximilian Espuny; José Salvador da Mota Reis; Elen Cristina Bravos Giupponi; Aglaé Baptista Torres Rocha; Ana Carolina Ferreira Costa; Camila Fabricio Poltronieri; Otávio José de Oliveira (Recycling)
The Circular Economy (CE) has become an essential management model to address the environmental challenges of the traditional linear model employed by companies, protecting society and ecosystems from resource depletion and intensified ecological emissions. Thus, this study proposes a framework with recommendations for CE implementation, structured around the Triple Helix (TH) model and designed to be government-led in guiding joint actions among government, organizations, and academia. The framework comprises 21 recommendations distributed across six interconnected stages: (1) Policy Generation from Academic Inputs, (2) Development of Pilot Projects with Industry, (3) Analysis and Academic Validation of Results, (4) Policy Improvement and Scaling, (5) Promotion of Innovation and Technology Transfer, and (6) Global Connection and Replicability. These stages collectively enhance policies and practices, accelerating the transition to a CE. This framework underscores the importance of regionally adapted public policies, technological innovations to extend material lifespans, and the promotion of conscious consumption. It also emphasizes the need for intersectoral collaboration to foster sustainability and efficiency in resource management. Methodologically, this study employs an integrative review to map technical and scientific CE practices in the United Kingdom, China, and the United States. The theoretical contribution validates the TH model as a strategic tool for developing the CE. Furthermore, the practical contribution is the structured pathway to implementing the CE, detailing the main phases of collaboration among TH actors to ensure the effective operationalization of circular strategies.